Online teaching practices that motivate and demotivate the students to learn - C. Lopez, Ariel; M. Albay, Eduard (International Journal of Evaluation and Research in Education (IJERE), 2025)
The rapid shift to online education during the COVID-19 pandemic has raised concerns about its impact on student motivation, particularly in mathematics education. This study investigates the online teaching practices that influence student motivation and demotivation. The primary objectives are to identify teaching practices that either motivate or demotivate students and to understand the challenges and benefits they encounter in an online learning environment. A qualitative approach was employed, utilizing document reviews and focus group discussions with third- and fourth-year students in the Philippines. Key findings reveal that engaging content, active participation, supportive teachers, and effective use of technology are significant motivators, while technical issues, lack of interaction, monotonous content, and insufficient feedback were the primary demotivators. To address these issues, the study proposes that educators should enhance interactive and supportive teaching practices while mitigating technical problems and fostering meaningful interactions. These recommendations aim to improve online teaching strategies and boost student motivation in digital learning environments.